Pengaruh Religiutas, Berkah Dan Pelayanan Terhadap Pilihan Pembayaran Zakat Di Lembaga Zakat Kota Salatiga dan Sekitatnya - Ahmad Mifdlol Muthohar (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
The main idea for this reseach is to see the points that motivate Muzakki to use the Zakat Institution to fulfill their zakat. These points mentioned above are the religious side (believe) of a Muzakki, the feeling of being blessed, and the service given by a Zakat through Zakat Instution to the Muzakki who has a preference on fulfilling zakat thorugh Zakat Instution. On this reseach, the method used os experimental method, and for this method, it involves 51 people from Salatiga and some regions around Salatiga. The analytical tools used here is the multiple regression analysis using Tobit model. The findings on this reseach are that the variance of religiosity and the feeling in blessings are not significantly affected by the choice of a Muzakki in using Zakat Instution. And variance of the service given by a zakat institution is signicantly affected by the choice of a Muzakki in using Zakat instution. Another finding is that from the total polling, 98% of the Muzakki say that they can feel the blessing when they fulfill the zakat, and this feeling is not related to the way of fulfilling their zakat, whether they go though the Zakat Institution or the do it themselves.